Determination of Physical Education and Sports Teachers' Nutrition Habits and Physical Activity Levels in the Global Epidemic (Covid-19) Process - Erdogan, Ramazan; Yilmaz, Metin; Aydemir, Isa (Asian Journal of Education and Training, 2021)
This research was conducted to determine Physical Education and Sports teachers' nutritional habits and physical activity levels during the global epidemic (covid-19) process. 156 (121 male, 35 female) volunteer physical education and sports teachers working in Elazig province participated in the study. In order to determine the demographic information of participants, the personal information form; to determine the nutritional habits and physical activity levels, the "Investigation of Nutrition Habits and Nutrition Knowledge Levels" developed by Yücel (2015) and to determine the physical activity levels, the short form of the "International Physical Activity Questionnaire" were applied to participants. The SPSS package program was used in the analysis of the data and the significance level was accepted as p<0.05. According to the research results, it was determined that 89.1% of physical education and sports teachers did not receive nutrition education, 62.2% had a chronic disease, 27.6% were in the age range 43 and above, 67.3% were married, 59% were between 171-180 cm, 38.5% were between 71-80 kg, 27.6% had a seniority between 6-10 years and 42,9% had income between 4001-5000 TL. 47.4% of the teachers stated the effect of the state's "Stay at Home" project on physical activity as no, 37.2% yes, 15.4% partially and most of them stated that body weight increased during the pandemic period. It was observed that the mean scores of the participants' nutritional habits before the pandemic were lower than their mean scores during the pandemic period and a statistically significant difference was determined (p <0.05). In addition, before the pandemic, it was seen that the physical activity score averages of the participants were higher than the physical activity score averages during the pandemic period, and statistically significance was determined (p<0.05). As a result, it was observed that the eating habits of the physical education and sports teachers participating in the study were negatively affected during the pandemic period, and their physical activity levels decreased. In this context, we believe that the promotion of regular physical activities as well as adequate and balanced nutrition during the epidemic period will contribute to the individuals to overcome the epidemic with minimum damage.